Did the entry of low cost companies foster the growth of strategic alliances in the airline industry? - Andra Mantovani; Ornella Tarola (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
In this paper we adopt a vertical differentiation model to study the effect of deregulation in the airline industry. In particular, we focus on the entry of low cost companies, which succeed in providing essential flight services at relatively cheap prices. We argue that the entry of very aggressive rivals pushed traditional carriers to react by forming strategic alliances and exploit economies of densities trough hub-and-spoke systems. We verify that a strategic alliance is profitable if the gain in terms of economies of density is sufficiently high and consumers' utility is not significantly decreased by the indirect connection.
Keywords: 330; Luftverkehr; Niedrigpreisstrategie; Strategische Allianz; Hub-and-Spoke-Netzwerk; Theorie